ASEAN Intergovernmental Commission on Human Rights and Effectiveness of Fulfilling Human Rights Obligations of ASEAN Members States - Budi Hermawan Bangun (Faculty of Law, Jambi University, 2018)
The inauguration of the ASEAN Declaration of Human Rights was inseparable from criticism from several parties, especially human rights organizations both within and outside ASEAN member states. This paper focuses on the function and mandate of the AICHR (ASEAN Intergovernmental Commission on Human Rights) and its influence on the effectiveness of the fulfillment of human rights obligations ASEAN member states. The results showed that within its mandate AICHR there is no balance between the functions of promotion and protection function because of the ambiguity of vision for an ASEAN Human Rights set the standard, which is between universal standards and particularist that maintains the principle of